Unconventional RNA‐binding proteins step into the virus–host battlefront. (9th August 2018) - Garcia‐Moreno, Manuel; Järvelin, Aino I.; Castello, Alfredo
Abstract : The crucial participation of cellular RNA‐binding proteins (RBPs) in virtually all steps of virus infection has been known for decades. However, most of the studies characterizing this phenomenon have focused on well‐established RBPs harboring classical RNA‐binding domains (RBDs). Recent proteome‐wide approaches have greatly expanded the census of RBPs, discovering hundreds of proteins that interact with RNA through unconventional RBDs. These domains include protein–protein interaction platforms, enzymatic cores, and intrinsically disordered regions. Here, we compared the experimentally determined census of RBPs to gene ontology terms and literature, finding that 472 proteins have previous links with viruses. We discuss what these proteins are and what their roles in infection might be. We also review some of the pioneering examples of unorthodox RBPs whose RNA‐binding activity has been shown to be critical for virus infection. Finally, we highlight the potential of these proteins for host‐based therapies against viruses. This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Interactions: Functional Implications RNA in Disease and Development > RNA in Disease RNA Interactions with Proteins and Other Molecules > RNA–Protein Complexes Abstract : The compendium of RNA‐binding proteins related to virus infection reveals an unexplored world of unconventional virus–host interactions.